1998
DOI: 10.2337/diacare.21.8.1317
|View full text |Cite
|
Sign up to set email alerts
|

Distortion-Product Otoacoustic Emissions and Selective Sensorineural Loss in IDDM

Abstract: Our results suggest that IDDM patients show an early abnormality of the micromechanical properties of the OHCs. In IDDM patients without a subclinical peripheral neuropathy, damage is limited to the higher frequencies and can be detected only by DPOAEs, whereas in IDDM patients with neuropathy, damage also involves the middle range of frequencies and can be detected by TEOAEs and DPOAEs. Therefore, DPOAEs seem to be able to detect the earliest cochlear selective-frequency dysfunction in IDDM patients without p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 24 publications
(38 reference statements)
2
25
1
4
Order By: Relevance
“…DPOAE was reduced below 2SD of control mean in 32% of diabetic patients, however no significant association between EOAEs and duration and control of diabetes was found. 11 The results of study conducted by Eren et al were contradictory to present study, in which no statistically significant difference is there between DPOAE amplitude (Ldp) between 40 diabetics and 24 control group in frequencies 1, 2, 2.5, 3,4, 5, 6, 7, and 8 kHz, however small study group can be a limitation of their study. 15 Bayindir et al investigated role of glycaemic control on outer hair cell functions.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…DPOAE was reduced below 2SD of control mean in 32% of diabetic patients, however no significant association between EOAEs and duration and control of diabetes was found. 11 The results of study conducted by Eren et al were contradictory to present study, in which no statistically significant difference is there between DPOAE amplitude (Ldp) between 40 diabetics and 24 control group in frequencies 1, 2, 2.5, 3,4, 5, 6, 7, and 8 kHz, however small study group can be a limitation of their study. 15 Bayindir et al investigated role of glycaemic control on outer hair cell functions.…”
Section: Discussioncontrasting
confidence: 54%
“…It is observed that the TEOAE recordings are not very frequency selective as compared to DPOAE. 10,11 In the present study, mean DPOAE SNR values for diabetics were lower in all frequencies [2000, 3000, 4000, 5000 and 6000 Hz] for diabetics. An early onset high frequency cochlear dysfunction in diabetics was indicated by lower SNR values with significant decrease for 4, 5 and 6 kHz.…”
Section: Discussionmentioning
confidence: 75%
“…The study conducted by Di Nardo et al 1998 [22] demonstrated that it was possible to verify a relationship between neuropathy and the amplitude of TOAE, as well as with the frequencies from 1 to 5 kHz of the DPOAE. However, in the group without neuropathy the correlation only occurred in frequencies from 3 to 5 kHz of DPOAE.…”
Section: Cochlear Dysfunction In Type 1 Dmmentioning
confidence: 99%
“…Hastalarda akustik şikayetler gelişmeden çok önce ABR değişiklikleri izlenebilir (10). ABR deki bozulmalar hastalığın süresi ile yakından ilişkilidir (6). Bununla birlikte periferik nöropatisi ve yaygın hastalığı olanlarda daha bozulmuş ABR sonuçları izlenmiştir (6).…”
unclassified
“…ABR deki bozulmalar hastalığın süresi ile yakından ilişkilidir (6). Bununla birlikte periferik nöropatisi ve yaygın hastalığı olanlarda daha bozulmuş ABR sonuçları izlenmiştir (6). Diabetik ensefalopatinin değerlendirilmesinde ve hastalığın yaygınlığının anlaşılabilmesinde ABR, IDDM'ta yararlı olabilir.…”
unclassified